2022
DOI: 10.1186/s10195-022-00629-8
|View full text |Cite
|
Sign up to set email alerts
|

Are additional screws required for press-fit fixation of cementless acetabular cups? A systematic review and meta-analysis

Abstract: Background Press-fit cementless acetabular cup is widely used in total hip arthroplasty (THA). However, the use of additional screws for the acetabular cup has been extensively debated. The purpose of this review is to compare the stability, revision rate, wear rate, and clinical scores of cementless acetabular cups with and without screws in THA. Materials and Methods Comprehensive literature searches of the following databases were performed: Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Although the measured outcomes showed no significant difference between the groups with and without the addition of screws in acetabular cup, in line with previous reviews [15][16][17], we concluded that the efficacy of acetabular cups without screw fixation remained uncertain, suggesting the need for prudent clinical application. Our conclusion was different from those of previous reviews.…”
Section: Summary Of Main Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Although the measured outcomes showed no significant difference between the groups with and without the addition of screws in acetabular cup, in line with previous reviews [15][16][17], we concluded that the efficacy of acetabular cups without screw fixation remained uncertain, suggesting the need for prudent clinical application. Our conclusion was different from those of previous reviews.…”
Section: Summary Of Main Resultssupporting
confidence: 86%
“…In the two previous systematic reviews, there was methodological concern regarding observational studies and RCTs being judged separately, and the effect size of these studies with different study designs was synthesized together. Subsequently, an earlier systematic review that synthesized the effect size from observational studies and RCTs separately reported that it was unnecessary to add screws to the acetabular cup [17]. However, duplication of participants was assumed because the same studies with different observation periods were synthesized in the osteolysis section.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the use of screws to supplement acetabular fixation is unsettled in literature, leaving the choice to surgeon preference. 24 As such, the purpose of this study was to assess acetabular migration between cups fixated with and without the use of screws. Initial cup position is an important determinant of THA success since cup malposition increases the risk of revision surgery, as it can lead to impingement, reduced range of motion, dislocation, wear and osteolysis, loosening and cup failure.…”
Section: Discussionmentioning
confidence: 99%
“…A research team based in Liaoning (China) did an excellent job of performing a thorough systematic review of all trials comparing outcomes in screw augmentation versus no screw in press-fit uncemented cups. 3 They identified 19 trials with 4,046 hip arthroplasties that had similar outcomes (stability, Harris Hip Score (HHS), and pain). They report that the meta-analysis showed no difference for: stability, osteolysis and migration, wear, revision rates, HHS, or pain.…”
Section: Are Additional Screws Required For Press-fit Fixation Of Cem...mentioning
confidence: 99%